PENERAPAN SISTEM PENDUKUNG KEPUTUSAN UNTUK SELEKSI MAHASISWA BERPRESTASI MENGGUNAKAN METODE AHP - Handayani, Titis (Jurnal Transformatika, 2012)
Decision support systems  play a role in helping the university to take appropriate decisions. In this study has made a Decision Support System for Selection of Student Achievement which serves to help the university take the right decision by using the method of Analytical Hierarchy Process (AHP). The main function of this system is to process the data selection of outstanding students college level.
Keywords: Decision Support System; Analytical Hierarchy Process